Strategi Guru dalam Membangun Kedisiplinan Belajar Siswa di Sekolah Dasar - Yuni, Febri; Dafit, Febrina (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe how the teacher's strategy in fostering student learning discipline as well as the factors that influence the learning discipline of third-grade students at State Elementary School 67 Pekanbaru. This type of research is descriptive qualitative research. Sources of data in this study are a third-grade guardian and all third-grade students. Data collection techniques in this study used interview, observation, and documentation techniques. Data analysis used the Milles and Huberman model with three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the strategies used by the teacher in building student learning discipline were guiding and directing student behavior in a positive direction, showing good disciplinary behavior in students, supervising all student behavior at school, controlling all student behavior at school, and giving appropriate punishments or rewards. constructive nature. Then, the factors that influence student learning discipline are internal factors and external factors. Internal factors are factors from within the students themselves and external factors, namely family environmental factors, school environmental factors, and community environmental factors.